2012
DOI: 10.1038/ki.2012.147
|View full text |Cite
|
Sign up to set email alerts
|

Activated innate immunity and the involvement of CX3CR1–fractalkine in promoting hematuria in patients with IgA nephropathy

Abstract: A hallmark of immunoglobulin A nephropathy (IgAN) is episodes of gross hematuria coinciding with mucosal infections that can represent the disease-triggering event. Here we performed a whole genomic screen of IgAN patients during gross hematuria to clarify the link between mucosal antigens and glomerular hematuria. Modulated genes showed a clear involvement of the intracellular interferon signaling, antigen-presenting pathway, and the immunoproteasome. The mRNA and protein level of the chemokine receptor chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(61 citation statements)
references
References 42 publications
2
59
0
Order By: Relevance
“…Recently, we reported that glomerular fraktalkine expression is involved in the pathogenesis and aggravation of childhood IgAN (Aizawa-Yashiro et al 2013;Tanaka and Imaizumi 2013). Furthermore, Cox et al (2012) have reported that increased glomerular expression of fraktalkine induces the onset of gross hematuria in adult patients with IgAN. However, the implications of both urinary fractalkine and MCP-1 concentrations in pediatric patients with GN remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, we reported that glomerular fraktalkine expression is involved in the pathogenesis and aggravation of childhood IgAN (Aizawa-Yashiro et al 2013;Tanaka and Imaizumi 2013). Furthermore, Cox et al (2012) have reported that increased glomerular expression of fraktalkine induces the onset of gross hematuria in adult patients with IgAN. However, the implications of both urinary fractalkine and MCP-1 concentrations in pediatric patients with GN remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Based on recent reports regarding the implications of expression of glomerular fractalkine in patients with IgAN (Cox et al 2012), fractalkine is thought to be a strong inducer of glomerular basement membrane (GBM) injury, resulting in massive hematuria. Thus, the urinary fractalkine concentration may be a predictor of inflammatory GBM damage in selected patients with GN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Episodes of MH are frequently triggered by mucosal infections, mainly of the upper respiratory tract. Recently, Cox et al [19] found that patients with RMH exhibit an upregulated expression of the chemokine receptor CX3CR1 in their circulating leukocytes during episodes of MH; IgAN patients who have permanent microscopic hematuria are characterized by low glomerular fractalkine (CX3CR1 ligand) expression. On the other hand, IgAN patients characterized by RMH have an enhanced fractalkine expression in both podocytes and endothelial cells and an enhanced urinary level of this chemokine.…”
Section: Discussionmentioning
confidence: 99%
“…Our recent experience on transcriptomics suggests that omics are available for creating specific classifiers in different diseases [19,20]. They are formed by a list of genes that are involved in the pathogenesis of the disease and they can be considered targeted genes for specific drugs [21].…”
Section: Expert Opinionmentioning
confidence: 99%